Role of National Service Scheme (NSS) in Creating Social Responsibility among Students of Higher Education - Yadav PhD, Pradeep Kumar (CV. Rayyan Dwi Bharata, 2025)
The N.S.S. camp activities will undoubtedly improve volunteers' communication skills, collective spirit, teamwork, and teamwork abilities. Students can engage in social activities on a daily basis through regular activity. It provides a link between the cognitive growth of students and the general instillation of reasoned values seeking in higher education. Students get the opportunity to comprehend societal issues and demands through the national service programme. N.S.S. volunteers use what they have learned from the past to the present to provide stronger leadership in the future. Our existence is fundamentally shaped by our values. Values reflect the changing aspect of culture and serve as a link between each individual and the social, cultural, and philosophical milieu of the community. Values come in many forms, such as universal, social, cultural, spiritual, and artistic values.